2017
DOI: 10.1186/s12884-017-1549-4
|View full text |Cite
|
Sign up to set email alerts
|

Histologic chorioamnionitis does not modulate the oxidative stress and antioxidant status in pregnancies complicated by spontaneous preterm delivery

Abstract: BackgroundInfection induced-inflammation and other risk factors for spontaneous preterm birth (PTB) and preterm premature rupture of membranes (pPROM) may cause a redox imbalance, increasing the release of free radicals and consuming antioxidant defenses. Oxidative stress, in turn, can initiate intracellular signaling cascades that increase the production of pro-inflammatory mediators.The objective of this study was to evaluate the oxidative damage to proteins and antioxidant capacity profiles in amniochorion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The competitive 3-nitrotyrosine (3-NT) ELISA Kit was used to determine protein peroxidation in plasma (OxiSelect™ Nitrotyrosine ELISA Kit, Cell Biolabs Inc., San Diego, USA). 3-NT is a product of posttranslational modification of protein tyrosine caused by peroxynitrite, and this modification can result in changes in protein structure, function, and catalytic activity [28]. The absorbance was read at 450 nm against 620 nm as a reference with an ELISA reader iMark™ (Bio-Rad USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The competitive 3-nitrotyrosine (3-NT) ELISA Kit was used to determine protein peroxidation in plasma (OxiSelect™ Nitrotyrosine ELISA Kit, Cell Biolabs Inc., San Diego, USA). 3-NT is a product of posttranslational modification of protein tyrosine caused by peroxynitrite, and this modification can result in changes in protein structure, function, and catalytic activity [28]. The absorbance was read at 450 nm against 620 nm as a reference with an ELISA reader iMark™ (Bio-Rad USA).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of protein carbonyl content is considered a reliable marker of oxidative protein damage due to its long-lasting stability [28]. Protein carbonyls were measured as a parameter of oxidative stress in plasma after derivatization with 2,4-dinitrophenylhydrazine (DNPH) with the Carbonyl Protein ELISA Kit (Immundiagnostik AG, Bensheim, Germany) according to the instructions supplied by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as is well-known, inflammation is a key point in parturition, even in the absence of intrauterine infection, and, in such cases, inflammation may come from the senescence of fetal membranes ( Behnia et al, 2016 ; Martin et al, 2017 ). Behnia et al (2015) found higher concentrations of pro-inflammatory SASP markers (granulocyte macrophage colony-stimulating factor and interleukin-6 and -8) in the amniotic fluid of women in labor at term than in women not in labor.…”
Section: Fetal Membranes Telomere-senescence In Parturition and Advermentioning
confidence: 99%
“…If chorioamnionitis is found in more than 20% of placenta specimens, the clinical significance increases. It may lead to preterm delivery, fetal and neonatal infection, respiratory distress, intrauterine hypoxia, and low APGAR score (1,2,21). In chorioamnionitis, the chronic villitis plays significant role in fetal infection; more than 30% of villous degeneration leads to perinatal death (1,2).…”
Section: Discussionmentioning
confidence: 99%